Studi Kasus pada Ibu Hamil Mual Muntah Trimester Pertama dengan Pemberian Seduhan Teh Daun Mint dan Madu di Puskesmas Rowosari - Renny Cantika Mithawati; Rahayu Utmaningsih; Tia Nurhanifah; Fajar Nuari Erwianisya (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Emesis gravidarum is a common condition experienced by pregnant women in the first trimester, which can interfere with health and quality of life. This study aims to evaluate the effectiveness of mint tea and honey in reducing symptoms of nausea and vomiting in pregnant women. This study used a case study design with the subject of a 20-year-old pregnant woman, G1P0A0, who was 9 weeks pregnant and experiencing emesis gravidarum. The intervention was carried out by giving 150 ml of mint tea and honey, once in the morning after meals, for three consecutive days. The study was conducted at Rowosari Health Center on November 19-22, 2024. Measurements were made using the PUQE observation sheet to assess the frequency and intensity of nausea and vomiting before and after the intervention. The results showed a significant decrease in the frequency of nausea and vomiting, from 4 times at the initial visit to 1 time at the third visit. The PUQE score also showed improvement from moderate to mild category. The administration of mint tea and honey proved effective in reducing symptoms of emesis gravidarum in first trimester pregnant women. This non-pharmacological method can be used to reduce nausea and vomiting in pregnant women.